2018
DOI: 10.1007/s11325-018-1682-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between insomnia and job stress: a meta-analysis

Abstract: The correlation between insomnia and higher levels of job stress, effort-reward imbalance, high demand, heavy workload, and low social support was determined. Publication bias and heterogeneity were partially observed. Furthermore, future studies with improved methodologies and a focus on mechanisms are anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(113 citation statements)
references
References 31 publications
6
101
1
5
Order By: Relevance
“…Meanwhile, they also observed that alcohol consumption in the quantity of >20 g/day, shift work and current illness were associated with insomnia in all the participants. Job stress is another risk factor of insomnia, which has been reported in many previous studies [18]. The results presented in this study found that steel workers with high stress and low social support were most likely to suffer from insomnia, and that steel workers struggling with stress had a higher risk of insomnia than steel workers without stress.…”
Section: Acknowledgmentssupporting
confidence: 74%
See 1 more Smart Citation
“…Meanwhile, they also observed that alcohol consumption in the quantity of >20 g/day, shift work and current illness were associated with insomnia in all the participants. Job stress is another risk factor of insomnia, which has been reported in many previous studies [18]. The results presented in this study found that steel workers with high stress and low social support were most likely to suffer from insomnia, and that steel workers struggling with stress had a higher risk of insomnia than steel workers without stress.…”
Section: Acknowledgmentssupporting
confidence: 74%
“…There are a lot of occupational hazards that can increase the risk of insomnia, such as hazardous gas, noise, hot environment, strenuous physical work, job stress, night work, etc. [17][18][19]. However, the prevalence of insomnia and its associated factors are rarely known in steel workers, especially in China.…”
Section: Questionnaire Measurementsmentioning
confidence: 99%
“…Self‐reported experience of sleeplessness before starting dental education doubled the odds for nervousness before working with patients and stress during it. A systematic review has shown that job stress increased the odds of insomnia . On the other hand, a recent study showed that sleeplessness is likely to mediate the association between school pressure and psychological symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, insomnia is one of the most prevalent occupational risks among the working population [ 6 , 7 ], being directly responsible for multiple impacts on workers’ health on both a physical and mental level [ 8 ]. Moreover, it has been proven that in the workplace, there is an association between insomnia and occupational accidents, productivity, presenteeism, sick leave, and work-related burnout [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%